Screw Stress Distribution in a Clavicle Fracture with Plate Fixation: A Finite Element Analysis - Angelo Alito; Domenico Fenga; Giada Tropeano; Demetrio Milardi; Danilo Leonetti; Alba Migliorato; Adriana Tisano; Danilo D’Andrea; Vincenzo Filardi (Bioengineering, 2023)
Clavicle midshaft fractures are mostly treated surgically by open internal reduction with a superior or anteroinferior plate and screws or by intramedullary nailing. Screw positioning plays a critical role in determining the stress distribution. There is a lack of data on the screw position and the appropriate number of cortices required for plate fixation. The aim of this study is to evaluate the mechanical behavior of an anterior plate implanted in a fractured bone subjected to 120° of lateral elevation compared to a healthy clavicle using numerical simulations. Contact forces and moments used were obtained from literature data and applied to the healthy and fractured finite element models. Stresses of about 9 MPa were found on the healthy clavicle, while values of about 15 MPa were calculated on the plate of the fractured one; these stress peaks were reached at about 30° and 70° of elevation when the stress shielding on the clavicle sums all the three components of the solicitation: compression, flexion, and torsion. The stress distribution in a clavicle fracture stabilized with plates and screws is influenced by several factors, including the plate’s position and design, the type of screw, and the biomechanical forces applied during movements.